Property, Power, and Authority in Rus and Latin Europe, ca. 1000-1236 - Mikhailova, Yulia (Assistant professor of history) (Book collections on Project MUSE., 2019)
"This book intertwines two themes in medieval studies, which so far have never been brought together: comparative studies of Latin and Orthodox Europe and a debate on the "feudal revolution" - the changes that occurred during the transition from Carolingian to post-Carolingian Europe. The book broadens the linguistic and geographical scope of the debate by comparing texts written in "learned" and "vulgar" Latin, Church Slavonic, Anglo-Norman, and East Slavonic, the vernacular of Kievan Rus. From this comparison, the Kingdom of the Rus' - a terra incognita for most medievalists, generally assumed to be profoundly different from the West -emerges as a regional variation of European society. In particular, the finding that contractual relations, traditionally described in scholarly literature as "feudo-vassalic," were present in the Kingdom of the Rus suggests that current explanations for the origins of such relations may overemphasize factors unique to the medieval West and overlook deeper pan-European processes."--Bloomsbury Publishing.